Complementary effect of co-doping aliovalent elements Bi and Sb in self-compensated SnTe-based thermoelectric materials. Issue 31 (15th July 2021) - Kihoi, Samuel Kimani; Shenoy, U. Sandhya; Bhat, D. Krishna; Lee, Ho Seong
Abstract : Engineering the electronic properties of SnTe through Bi and Sb co-doping to improve the thermoelectric performance. Abstract : Research on Pb-free thermoelectric materials as a potential eco-friendly and solid-state source of energy has continuously advanced over time, with SnTe-based materials having shown utmost promising properties owing to their tunable electronic structure and scalable thermal conductivity. In this study, we self-compensate Sn to reduce inherent Sn vacancies, and further tune the carrier concentration by doping with Bi. Sb is further alloyed to incorporate nanostructures that significantly reduce the thermal conductivity. Multiple aliovalent dopants result in a continually decreased carrier concentration and subsequent significantly decreased electrical conductivity. The Seebeck values are seen to increase with temperature, where a maximum value of ∼171 μV K −1 is reported with a maximum power factor of ∼22.7 μW cm −1 K −2 . We show through first principles DFT calculations the synergistic effect of Bi and Sb to introduce resonance states and an additional valence band convergence effect with increasing Sb that contribute to improved electronic properties. A decreased phonon frequency with co-doping is also reported. A maximum ZT of ∼0.8 at 823 K is reported in the Sn0.90 Bi0.03 Sb0.10 Te composition, showing good potential in Sb co-doped SnTe-based materials.